Measuring In-Hospital Recovery After Colorectal Surgery Within a Well-Established Enhanced Recovery Pathway: A Comparison Between Hospital Length of Stay and Time to Readiness for Discharge. Issue 7 (July 2018) - Balvardi, Saba; Pecorelli, Nicolò; Castelino, Tanya; Niculiseanu, Petru; Liberman, A. Sender; Charlebois, Patrick; Stein, Barry; Carli, Franco; Mayo, Nancy E.; Feldman, Liane S.; Fiore, Julio F.
Abstract : BACKGROUND: Hospital length of stay is often used as a measure of in-hospital recovery but may be confounded by organizational factors. Time to readiness for discharge may provide a superior index of recovery. OBJECTIVE: The purpose of this study was to contribute evidence for the construct validity of time to readiness for discharge and length of stay as measures of in-hospital recovery after colorectal surgery in the context of a well-established enhanced recovery pathway. DESIGN: This was an observational validation study designed according to the COnsensus-based Standards for the selection of health status Measurement INstruments (COSMIN) checklist. SETTINGS: The study was conducted at a university-affiliated tertiary hospital. PATIENTS: A total of 100 consecutive patients undergoing elective colorectal resection (mean age = 65 y; 57% men; 81% laparoscopic) who participated in a randomized controlled trial were included. MAIN OUTCOME MEASURES: We tested a priori hypotheses that length of stay and time-to-readiness for discharge are longer in patients undergoing open surgery, with lower physical status, with severe comorbidities, with postoperative complications, undergoing rectal surgery, who are older (≥75 y), who have a new stoma, and who have inflammatory bowel disease. RESULTS: Median time-to-readiness for discharge and length of stay were both 3 days. For both measures, 6 of 8 construct validity hypotheses were supported (hypotheses 1 and 4–8). LIMITATIONS: The use of secondary data from a randomized controlled trial (risk of selection bias) was a limitation. Results may not be generalizable to institutions where patient care is not equally structured. CONCLUSIONS: This study contributes evidence to the construct validity of time-to-readiness for discharge and length of stay as measures of in-hospital recovery within enhanced recovery pathways. Our findings suggest that length of stay can be a less resource-intensive and equally construct-valid index of in-hospital recovery compared with time-to-readiness for discharge. Enhanced recovery pathways may decrease process-of-care variances that impact length of stay, allowing more timely discharge once discharge criteria are achieved. SeeVideo Abstract athttp://links.lww.com/DCR/A564 . Abstract : Supplemental Digital Content is available in the text.